2013
DOI: 10.1002/mds.25438
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire‐based diagnosis of REM sleep behavior disorder in Parkinson's disease

Abstract: A combination of patient and bed-partner questionnaires is a useful tool to detect RBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…In order to increase the sensitivity of the clinical diagnosis, two different screening tools were used to detect the presence of symptoms of RBD, namely the recently published RBD1Q20 and the RBDSQ 21. The latter has shown fair internal consistency in patients with PD and a good validity for the screening of RBD in this population, with a recommended cut-off of six points22 Indeed, its sensitivity in patients with PD, when compared to the diagnosis made according to ICDS-II criteria, ranges from 74% to 84%, while its specificity ranges from 63% to 96% in two different studies 22 41. Sensitivity and specificity of RBD1Q, however, have not been formally assessed in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the sensitivity of the clinical diagnosis, two different screening tools were used to detect the presence of symptoms of RBD, namely the recently published RBD1Q20 and the RBDSQ 21. The latter has shown fair internal consistency in patients with PD and a good validity for the screening of RBD in this population, with a recommended cut-off of six points22 Indeed, its sensitivity in patients with PD, when compared to the diagnosis made according to ICDS-II criteria, ranges from 74% to 84%, while its specificity ranges from 63% to 96% in two different studies 22 41. Sensitivity and specificity of RBD1Q, however, have not been formally assessed in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Constipation Module and calculated both the total score and the isolated sum of the constipation items (questions 9–14) [2, 22]. We investigated sleeping habits using the REM sleep behavior disorder screening questionnaire (RBDSQ) [23]. Salivary symptoms were evaluated using the Drooling Rating Scale (DRS) [24].…”
Section: Methodsmentioning
confidence: 99%
“…A cut-off score of 5 was reported by the authors as most useful when differentiating patients with idiopathic RBD from controls 12. As this cut-off is only associated with a specificity of 0.56,12 sensitivity analyses were also performed using a RBDSQ cut-off of 6 and 7, in the light of subsequent validation studies that found stronger test performance characteristics using these higher cut-offs 13 14…”
Section: Methodsmentioning
confidence: 99%